In vitro and in silico assessment of RF‐induced heating around intracranial aneurysm clips at 7 Tesla. Issue 1 (7th March 2017) - Noureddine, Yacine; Kraff, Oliver; Ladd, Mark E.; Wrede, Karsten H.; Chen, Bixia; Quick, Harald H.; Schaefers, Gregor; Bitz, Andreas K.
Abstract : Purpose: To examine radiofrequency‐induced tissue heating around intracranial aneurysm clips during a 7 Tesla (T) head MR examination. Methods: Radiofrequency (RF), temperature simulations, and RF measurements were employed to investigate the effects of polarization and clip length on the electric field (E‐field) and temperature. Heating in body models was studied using both a conservative approach and realistic exposure scenarios. Results: Worst‐case orientation was found for clips aligned parallel to the E‐field polarization. Absolute tissue temperature remained below International Electrotechnical Commission regulatory limits for 44 of 50 clinical scenarios. No significant effect on heating was determined for clip lengths below 18.8 mm, and worst‐case heating was found for clip length 51.5 mm. The conservative approach led to a maximum permissible E‐field of 72 V/m corresponding to B 1 + of 1.2 µT, and an accepted power of 4.6 W for the considered RF head coil instead of 38.5 W without clip. Conclusion: Safe scanning conditions with respect to RF‐induced heating can be applied depending on the information about the clip gained during screening interviews. However, force and torque measurements in the MR system shall be conducted to give a final statement on the MR safety of aneurysm clips at 7T. Magn Reson Med 79:568–581, 2018. © 2017 International Society for Magnetic Resonance in Medicine.